Anteseden dan Outcome dari Neglectful Parenting: Systematic Literature Review - Wardah Nabilah Munayya; Nida Hasanati (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to comprehensively examine the antecedents and outcomes of neglectful parenting, a parenting style characterized by low emotional involvement, inadequate supervision, and insufficient fulfillment of adolescents’ physical and psychological needs. A Systematic Literature Review (SLR) approach was employed, following the PRISMA guidelines, including identification, screening, eligibility assessment, and final inclusion. An initial search identified 450 scholarly articles published in national and international journals indexed in Scopus, PubMed, and Google Scholar. After applying rigorous inclusion and exclusion criteria, 14 high-quality empirical studies were selected for in-depth analysis. The findings consistently indicate that neglectful parenting is significantly associated with various adverse outcomes in adolescents, including increased vulnerability to mental health problems, engagement in delinquent behaviors, academic underachievement, and impairments in emotional and social development. Furthermore, this review identifies several key antecedent factors contributing to the emergence of neglectful parenting practices, such as high parental stress, socioeconomic hardship, low parental educational attainment, and limited social support systems. These results suggest that neglectful parenting is a multidimensional phenomenon shaped by the complex interaction of individual, familial, and broader social contexts. The study highlights the critical need for family-based preventive and intervention strategies, as well as social policies aimed at strengthening parental capacity and well-being. Addressing the antecedents of neglectful parenting is essential to mitigating its long-term negative consequences and promoting healthier developmental outcomes among adolescents.